ANALISA UNJUK KERJA KONDENSOR PADA PLTU TANJUNG JATI B UNIT 3 DAN 4 - , RIDHO SATRIANA; , Ir.Tarmono, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heat exchanger is a device used to transfer heat from one fluid to another fluid. One of the heat exchangers in the Tanjung Jati B Power Plant Units 3 and 4 are on the condenser which serves to cool or condense low pressure steam turbine output by using sea water as the cooling fluid. The condenser is a major component in the system, when the power plant is having problems then it will reduce of power plant efficiency. Given the importance of the condenser in a steam power plant cycle, it is necessary to know how the performance of the condenser, especially when performance after outage (maintenance), where the purpose of this outage is to improve the performance of the condenser whether successfully implemented or not. The method used in this condenser performance analysis is the calculation of the value of effectiveness and efficiency by using two different power plant load conditions as a comparison. Comparing conditions before and after the outage is implemented on the condenser of unit 3, and compare the performance between the condenser of unit 3 and unit 4 after the outage. Outage has been done successfully improve the performance of the condenser in unit 3 , marked by increasing efficiency condenser by 0.5% at 539 MW of power plant load , and also after the outage the efficiency of the condenser in unit 3 is higher than the efficiency of the condenser unit 4 by a margin of 1.6% on the load 535 MW.